Rethinking Geographical Indication Law: Lessons from EU Success and Lobong Pineapple - Kalalo, Merry Elisabeth; Kapugu, Betsy Anggreni; Turangan, Doortje Doerien; Ehirim, Ugochukwu Godspower (Universitas Negeri Gorontalo, 2025)
Indonesia’s Geographical Indication (GI) regime exhibits a persistent gap between formal legal eligibility and practical enforceability, particularly in rural contexts where institutional coordination and legal literacy remain limited. The case of Lobong Pineapple, a product with clear geographical specificity and socio-economic potential, underscores the systemic failure of the GI framework to translate normative protection into actionable development. This study aims to critically examine the regulatory and institutional barriers that hinder GI implementation in Indonesia, using Lobong Pineapple as a representative case. Employing a normative legal method complemented by comparative and empirical analysis, this research evaluates Indonesian GI law against successful practices in the European Union. The findings reveal that despite meeting substantive GI criteria, Lobong Pineapple remains unregistered due to administrative inertia, fragmented local governance, and the absence of enabling legal instruments such as a Regent’s Decree and product specification dossier. In contrast, the EU model demonstrates how institutional synergy, community participation, and integration with rural development policies can operationalize GI law effectively. This study offers a novel reconceptualization of GI protection as a transformative legal infrastructure—one that extends beyond protectionist aims to encompass cultural continuity, economic inclusion, and creative innovation. It proposes a shift from centralized, compliance-driven models to adaptive, community-anchored governance frameworks. By advancing this normative and structural critique, the research contributes to the refinement of intellectual property law as a tool for territorially embedded, culturally sensitive, and development-oriented legal reform.